Investigation and control of lumpy skin virus by taking symptomatic and asymptomatic measures using Mittag-Lefller kernel - Alhefthi, Reem K.; Ahmad, Aqeel; Farooq, Qazi Muhammad; İnç, Mustafa; Rezapour, Shahram; Ghaffar, Abdul (Springer, 2025)
Mathematical formulations play a crucial role in comprehending the dynamics of disease spread within a community. The objective of this research is to investigate the lumpy skin disease spread in cattle by taking control strategy as well as symptomatic and asymptomatic measures. The newly developed SVEI1I2R\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$SVEI_1I_2R$$\end{document} system is examined both qualitatively and quantitatively to ascertain its stable state. Local stability of the developed system is investigated for the validity of the developed system. The positiveness and existence of solution for the developed model are examined to ensure reliable findings, which are essential properties of epidemic models. The global derivative is illustrated to confirm the positivity with linear growth and Lipschitz conditions for the rate of effects in each sub-compartment on a global scale. The system is examined for global stability using Lyapunov first derivative functions to evaluate the collective impact of additional infections for acute as well as chronic stage. Simulations are conducted to observe the symptomatic and asymptomatic effects of the Lumpy skin disease acute as well as chronic infections worldwide in the cattle animals, providing insights into the actual behavior of the disease spread for both level acute as well as chronic. These investigations are valuable for comprehending the virus's spread and effective control strategies at early detection or on acute stage infection from our justified outcomes.
Keywords: Mathematical modeling; Stability analysis; Existing and positiveness; Lipschitz conditions; Global derivative